MENGENAL SIAPA AKU DALAM MEMBANGUN ATAU MENGEMBANGKAN ILMU PENGETAHUAN (=AKUNTANSI) - Suardikha, I Made Sadha (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 2 (2015), 2015)
I’m in question who I am? is the supreme consciousness that reached by humans, which is a true self that blends or single source, is something that can not be explained, but it seems there is none. So I’m in the question who I am? is something there but no, that is God. Build or develop science (= accounting) through human activity which is the abode of I, which is God, can be done through a profession or Swadharma each man himself. Profession man used as a means to build or develop science (= accounting) is related to the accounting profession.
Keywords: who I am?, build or develop, science, accounting